Bilateral idiopathic orbital inflammation 3 years before systemic Wegener´s granulomatosis in a 7-year-old girl - Juan D Martínez-Gutiérrez (Dove Medical Press, 2008)
Juan D Martínez-Gutiérrez1, Enrique Mencía-Gutiérrez1, Esperanza Gutiérrez-Díaz1, José L Rodríguez-Peralto2Departments of 1Ophthalmology and 2Pathology, 12 de Octubre Hospital, Complutense University, Madrid, SpainAbstract: Wegener’s granulomatosis (WG) is a necrotizing granulomatous vasculitis characterized by the involvement of the upper or lower airways, lungs, and kidneys, but it can affect almost any organ including the orbit. WG is rare in childhood. This case report describes a 7-year-old girl who presented bilateral idiophatic orbital inflammation and antineutrophil cytoplasmic antibodies-negative titres. Computed tomography scan and magnetic resonance imaging showed enlargement of both lacrimal glands with infiltration. Treatment with corticosteroids achieved remission of the disease. Three years later, she developed a systemic affectation with tracheal stenosis, pulmonary affectation, renal failure, and respiratory tract mucosa inflammation. Lacrimal gland biopsy showed perivascular nonspecific granulomas and ANCA titres remain negative. Treatment with corticosteroids and cyclophosphamide was done. A relapse occurred 2 years later, with complete remission with antitumor necrosis factor-alpha. No other symptoms have appeared after 9 years of follow-up. Early diagnosis and treatment is crucial to increase the survival rate in these patients.Keywords: ANCA, children, idiopathic orbital inflammation, exophthalmos, vasculitis, Wegener’s granulomatosis